2018
DOI: 10.5116/ijme.5be5.8131
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, burnout, and declining medical career interest among undergraduate pre-medical students

Abstract: Objectives To investigate the relationship between mental health issues and medical career interest among undergraduate premedical students, and to explore whether this association varies by gender. Methods A longitudinal survey of freshman and sophomore premedical students at Indiana University was conducted during the 2015-16 academic year. Survey data were collected from 390 respondents via an online questionnaire (response rate=14%) in September 2015, and 292 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
2
25
2
5
Order By: Relevance
“…[39] In terms of student wellness, each aspect of the ORS measure declined going from 2018-2019 to 2019-2020, and although there wasn't a drastic change at McGill in terms of how classes were run, studies have shown that depressive symptoms and burnout are increasing amongst college students. [40] This is also consistent with our ndings of a larger number of upper-year university students using our service as compared to rst-year students. This nding may be preliminary evidence indicating that rates of mental health among university students are indeed decreasing over time.…”
Section: Discussionsupporting
confidence: 91%
“…[39] In terms of student wellness, each aspect of the ORS measure declined going from 2018-2019 to 2019-2020, and although there wasn't a drastic change at McGill in terms of how classes were run, studies have shown that depressive symptoms and burnout are increasing amongst college students. [40] This is also consistent with our ndings of a larger number of upper-year university students using our service as compared to rst-year students. This nding may be preliminary evidence indicating that rates of mental health among university students are indeed decreasing over time.…”
Section: Discussionsupporting
confidence: 91%
“…Also it is in agreement with Santen et al results [ 9 ], where the authors affirm that one-third of all medical student show a moderate or high degree of burnout, being 43% of the third-year class. These higher levels of burnout during the development of the medical degree are associated to lower interest for the medical profession [ 17 ], which may lead to worse medical performance associated to lower levels of empathy among future physicians [ 18 , 19 ] that finally leads to worsen medical performance [ 20 ]. This is one of the reasons why it has been suggested that burnout in physicians is rooted in their formative period [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also it is in agreement with Santen et al results [9], where the authors a rm that one-third of all medical student show a moderate or high degree of burnout, being 43% of the third-year class. These higher levels of burnout during the development of the medical degree are associated to lower interest for the medical profession [19], which may lead to worse medical performance associated to lower levels of empathy among future physicians [20,21] that nally leads to worsen medical performance [22]. This is one of the reasons why it has been suggested that burnout in physicians is rooted in their formative period [23].…”
Section: Discussionmentioning
confidence: 99%